Recent Advances in Biotechnological Methods for Wheat Gluten Immunotoxicity Abolishment – a Review - Vijole Bradauskiene; Lina Vaiciulyte-Funk; Bakht Ramin Shah; Darius Cernauskas; Mihaela Adriana Tita (Polish Journal of Food and Nutrition Sciences)
Due to the increasing incidence of gluten intolerance, researchers are focusing on finding ways to eliminate immunotoxicity of wheat, this would allow the use of wheat products for gluten-intolerant consumers. The article reviews recent studies on biotechnological methods to eliminate and reduce the immunogenicity of wheat products. So far, many gluten removal methods have been proposed, but their efficacy levels were quite different. Enzymatic treatment of gluten fragments can be considered the simplest and non-invasive tool to eliminate the toxicity of gliadins and glutenins. For this purpose, various endogenous enzymes derived from cereals, and also those of bacterial, fungal, plant, and animal origin can be used in food processing. Some of the enzymes hydrolyze gluten, others block the action of toxic protein fragments. The majority of studies were carried out using lactic acid bacteria cultures, as single strains or in consortia. Satisfactory results have been achieved using bacterial and plant enzymes, but the complete elimination of gluten immunogenicity is still possible by using fungal proteases, engineered enzymes or combining several treatments, for example, by using lactic acid fermentation or germination with fungal proteases. However, the question of how degradation of gluten affects the quality of flour (dough) in practice remains unanswered. It is not clear whether the products of such wheat flour are better and safer than those made from starches and whether their price and quality are acceptable to consumers. The insights presented in this review will be helpful to other researchers and cereal-based food producers in choosing ways to reduce gluten immunogenicity.